Osteosarcoma: a review of current and future therapeutic approaches - Zhao, Xin (Biomed Eng Online, 2021)
Osteosarcoma (OS) is the most common primary bone malignancy that affects children and young adults. OS is characterized by a high degree of malignancy, strong invasiveness, rapid disease progression, and extremely high mortality rate; it is considered as a serious threat to the human health globally. The incidence of OS is common in the metaphysis of long tubular bones, but rare in the spine, pelvis, and sacrum areas; moreover, majority of the OS patients present with only a single lesion. OS has a bimodal distribution pattern, that is, its incidence peaks in the second decade of life and in late adulthood. We examine historical and current literature to present a succinct review of OS. In this review, we have discussed the types, clinical diagnosis, and modern and future treatment methods of OS. The purpose of this article is to inspire new ideas to develop more effective therapeutic options.